Library studies in crisis - Grygrowski, Dariusz (Interdyscyplinarium nauk o mediach i kulturze, 2020)
The purpose of this article is to analyse the situation in Polish higher education institutions which offer studies in library and information science in the period of reforming the higher education in Poland. A literature review has been carried out concerning education in the field of library and information science. Selected legal acts regarding libraries and higher education law have also been analysed, as well as information from the websites of academic centres of book studies and information science. Some of the centres conducting studies in the field of information and library science have been closed down. Most of the other academic centres of book studies and information science no longer conduct the “library and information science” studies, replacing them with courses focused more on issues relating specifically to information science. The studies in library and information science in Poland are currently in crisis. The decrease in the number of academic centres conducting such studies was significantly influenced by legal acts concerning the fields of study available at universities, a deregulation of the librarian’s profession and a new classification of academic disciplines.